Assessing the TP53 marker type in patients treated with or without neoadjuvant chemotherapy for resectable colorectal liver metastases: A p53 Research Group study. Issue 5 (May 2015) - Pilat, N.; Grünberger, T.; Längle, F.; Mittlböck, M.; Perisanidis, B.; Kappel, S.; Wolf, B.; Starlinger, P.; Kührer, I.; Mühlbacher, F.; Kandioler, D.
Abstract The type of a biomarker – whether it is prognostic or predictive – is frequently not known, although such information is crucial for assessing the clinical value of a marker. In order to evaluate the type of marker TP53 is, we identified a cohort of 76 patients with colorectal liver metastases (CLM), homogeneously staged as resectable, who had been treated either with or without fluorouracil-based neoadjuvant chemotherapy. The TP53 genotype was assessed retrospectively from paraffin-embedded, diagnostic tumour biopsies using a standardised, p53 gene-specific sequencing protocol (mark53® kit). The overall median survival was 44.2 months, and the overall TP53 mutation frequency was 55%. A significant interaction was observed between chemotherapy and TP53 status (P = 0.045). To illustrate this effect, the 51 patients with and the 25 patients without neoadjuvant chemotherapy were described separately. In patients with neoadjuvant chemotherapy, mutated TP53 was significantly associated with poor survival (P = 0.0025), resulting in five-year survival rates of 22%, compared to 60% in patients with normal TP53. The hazard ratio was 3.12 (95% confidence intervals (CI): 1.46–6.95) to the disadvantage of TP53-mutated patients and 5.49 (P = 0.0001; 95% CI: 2.28–13.24) after adjustment for known prognostic factors. In patients treated with surgery alone, a mutated TP53 did not have a negative effect on survival (P = 0.54). A mutated TP53 status independently predicted survival disadvantage in CLM patients in the presence, but not in the absence, of neoadjuvant chemotherapy. Our data suggest that TP53 might be a pure predictive marker.